El mundo alucinante: the Construction of Dissidence (Anclajes, 2011)
Reinaldo Arenas’s novel, El mundo alucinante (1966), shapes a complex fiction, history and autobiography scheme. Criticism often highlights the connection between life and work as a distinctive feature in Arenas’s production, focusing on the striking coincidence between the contents of this early novel and the subsequent facts in the writer’s life. Considering this idea as a starting point, the article proposes that El mundo alucinante builds up a dissident place in its own narrative scheme instead of containing signs about the novelist’s future.  This paper first reinstates the publication scene of the book, and then analyses some narrative textual aspects in detail, especially those that add to the representation strategies.
Keywords: Reinaldo Arenas; El mundo alucinante; representation; dissidence; autofiguration